THE ANTECEDENTS OF TAX EVASION PERCEPTION WITH A RELIGIOUSITY AS MODERATION - Tandry Whittleliang Hakki; Jobrinson Simanungkalit; Mung Siat (Kajian Akuntansi, 2023)
Tax evasion is an act of taxpayers who always try to minimize their tax burden by violating the provisions of the tax laws. This study aims to analyze the effect of the self-assessment system, money ethics, and discrimination on the perception of taxpayers by mediating religiosity. The population of this research is individual taxpayers in DKI Jakarta. The primary data used is in the form of questionnaires distributed to 150 respondents (taxpayers), of which 135 questionnaires are returned and can be processed for research results. The sampling technique used in this study is purposive sampling, while the data analysis methods used are descriptive analysis and multiple linear regression analysis. The results of the study show that the self-assessment system has an effect on tax evasion, but money ethics has no effect on tax evasion. This study also concludes that religiosity strengthens the effect of the self-assessment tax system on perceptions of tax avoidance and religiosity does not play a moderating role between money ethics and tax evasion. Keywords: Money Ethics, Tax Self Assessment System, Perception of Tax Evasion, Religiosity.